(untitled) (Revista Brasileira de Ciências Farmacêuticas, 2002)
Isotretinoin, or 13-cis-retinoic acid, is one of the vitamin A related compounds. Isotretinoin is used for the treatment of severe cystic acne and also shows inhibitory activity over the proliferation of neoplasic cells, due to its efficiency in regulating cell diferentiation. Side effects are related to skin and mucous membranes, central nervous system, muscles, lymphatic, gastrintestinal, pulmonary and genitourinary systems. Isotretinoin is a highly thermal and photolabile compound. Stability studies require several analytical methods such as HPLC, GC, thermal analysis, mass spectrometry, microcalorimetry and X-Ray difratometry.